Exploratory pilot testing of the psychometric properties of the person engagement index instrument among older, community-dwelling adults - Ellen Swartwout; Taya Irizarry; Annette Dabbs; Scott Barnett (The Beryl Institute, 2017)
The objective of this paper was to evaluate the psychometric properties of the Person Engagement Index with community dwelling older adults and determine the factors that impact this population's capacity to engage in healthcare. This non-experimental pilot evaluation of the psychometrics of the Person Engagement Index was performed in a convenience sample of 100 community-dwelling older adults. Exploratory factor analysis was conducted using dimension reduction to determine the underlying structure of a person's capacity to engage in healthcare. Results indicated good internal consistency with Cronbach's alpha=.882 for the overall scale. Exploratory factor analysis with varimax rotation was conducted resulting in a five-factor solution. Four of the five subscales exceeded Cronbach's alpha > .70 threshold for internal consistency. Cronbach's alpha results for the five domains were: (Knowledge of Healthcare Status) =.886, (Proactive Approach to Healthcare) =.780, (Motivation to Manage Healthcare) =.742, (Psychosocial Support for Healthcare) =.658 and (Technology Use in Healthcare) =.796. Results suggest that the Person Engagement Index instrument is a valid and reliable instrument to measure a person's capacity to engage in healthcare among community dwelling older adults. Testing in different settings with other populations and over time is warranted to further explore the reliability and validity of the Person Engagement Index for different subgroups and its sensitivity to changes in health status that may impact a person's capacity to engage in care.